2016
DOI: 10.1155/2016/4370674
|View full text |Cite
|
Sign up to set email alerts
|

Nonmotor Features in Parkinson’s Disease: What Are the Most Important Associated Factors?

Abstract: Introduction. The purpose of this study was to demonstrate the frequency and severity of nonmotor symptoms and their correlations with a wide range of demographic and clinical factors in a large cohort of patients with Parkinson's disease (PD). Methods. 268 PD patients were assessed using the validated Movement Disorders Society's Unified Parkinson's Disease Rating Scale (MDS-UPDRS), the Beck Depression Inventory (BDI), Parkinson's Disease Questionnaire (PDQ-39), the Hoehn and Yahr scale (HY), the Schwab and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 43 publications
6
31
0
Order By: Relevance
“…Many experience fluctuating motor as well as nonmotor symptoms of disease that will negatively impact daily life, both for the persons with PD and their relatives. Nonmotor symptoms often do not respond as well as motor symptoms to medical treatment (Prakash, Nadkarni, Lye, Yong, & Tan, 2016), and available pharmacotherapy often results in complications such as behavioural symptoms, motor fluctuations, dyskinesias and painful dystonia (Kadastik-Eerme et al, 2016). Although persons with PD and their relatives have a long-term need for close and regular contact with health care, treatment and care are performed mostly by the person affected with PD and his/her relatives in the community and in everyday life (Beaudet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many experience fluctuating motor as well as nonmotor symptoms of disease that will negatively impact daily life, both for the persons with PD and their relatives. Nonmotor symptoms often do not respond as well as motor symptoms to medical treatment (Prakash, Nadkarni, Lye, Yong, & Tan, 2016), and available pharmacotherapy often results in complications such as behavioural symptoms, motor fluctuations, dyskinesias and painful dystonia (Kadastik-Eerme et al, 2016). Although persons with PD and their relatives have a long-term need for close and regular contact with health care, treatment and care are performed mostly by the person affected with PD and his/her relatives in the community and in everyday life (Beaudet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The standard medication of PD is levodopa. However, the effect of treatment decreases with time, and after 5-10 years, treatment complications may occur [4,5,26]. Earlier studies have shown that most patients with PD produce less saliva compared to healthy controls [10,16,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical diagnosis of PD is based upon a defined motor syndrome (bradykinesia, rigidity, rest tremor), also, non-motor features are present in most patients in the early stages of the disease already, and often can dominate among clinical manifestations [1][2][3]. As the disease progresses, the burden of non-motor symptoms rises, affecting substantially the quality of life of patients with PD [4,5]. Some of the nonmotor features, such as autonomic and neuropsychiatric disturbances, seem to preferentially affect patients with nontremor-dominant subtypes of PD [6].…”
Section: Introductionmentioning
confidence: 99%
“…4 PD is caused by a critical loss of dopamine in the forebrain, which results in typical cardinal motor symptoms such as tremor, postural instability, muscular rigidity, and bradykinesia/hypokinesia. 5 In addition, common nonmotor symptoms such as autonomic dysfunctions, sleep disturbances, and olfactory symptoms are critical factors that degrade the quality of life (QoL) of PD patients 6 and make the pathology severely disabling, both physically and socially. 7,8 The long-term development of the disease, expression of symptomatic complications (e.g., motor fluctuations) during specific times of day, long waiting lists, and traveling costs (particularly for people who live in rural areas) are just a few reasons that support the need to move Parkinson's care into the home and to develop new care models.…”
Section: Au2mentioning
confidence: 99%